Model-based Design of a Subsurface Wetland for Water Quality Improvement of the Inflow River of Baiyangdian Lake, China - Xu, Fei; Zhao, Yanwei (Journal of Environmental Accounting and Management, 2026)
The decline of water quality of the inflow river has direct negative impact on the ecological conditions of lake ecosystem. The design of subsurface wetlands was considered to be an effective method for improving the water quality of inflow rivers, especially reducing the excessive nutrients to alleviate eutrophication. A subsurface wetland was designed by applying the wetland model Subwet 2.0 for treating the polluted inflow river— Fu River of Baiyangdian Lake. The simulation scenarios concerning the changes of wetland area were designed to find out the treatment effect of the subsurface wetland. The variation trends of the effluent concentrations of BOD5, ammonium, total nitrogen and total phosphorus for the scenarios had been obtained. The area and volume of the wetland which are the core design parameters have been determined through comparing the reduction percentages of the main pollutants under different design scenarios. The results showed that the simulation results in scenario 2 can simultaneously satisfy the conditions that the efficiencies of removal of total nitrogen and total phosphorus should reach to 90% in the Fu River and meanwhile less time, which is considered as the optimal design scheme. The area and volume should be set as 875m2and 525m3 to make the water quality standard of Fu River change from class V to class III, which could greatly control the eutrophication of Baiyangdian Lake. The method of wetland design based on model could reduce the uncertainties of traditional wetland design method and facilitate the water quality improvement of aquatic ecosystems.